A Noble Pity. ἔλεος in Plato’s Philosophy - Santiago Eslava - Bejarano (Vox Patrum, 2022)
This article examines Plato’s remarks on compassion to show that his apparent rejection of this emotion is, in fact, a rejection of a kind of ill-founded compassion. In the first section, I argue that his criticisms in the Apology and the Republic are not directed to compassion per se, but to instances in which this emotion betrays false beliefs and is felt in improper contexts. Thus, Plato’s criticisms leave room for an appropriate type of pity that should be grounded on true beliefs about harm, virtue, and justice. In the second section, I address Plato’s remarks on compassion in the Gorgias and the Laws, where he asserts that it should be felt towards the unpunished wrongdoer. I argue that such a disposition to feel compassion appropriately - which I have called a “noble compassion”, akin to the “noble anger” (θυμός γενναῖος) present in the Laws – is an important feature of the character of an ideal citizen. Thus, for Plato, compassion could contribute to psychological well-being and social order. By inspecting the cognitive and contextual conditions that enable a noble compassion in Platonic philosophy, this article aims to contribute to the study of a crucial emotion both in Greek and Christian philosophy.